Radiocarbon dating of charcoal from tropical sequences: results from the Niah Great Cave, Sarawak, and their broader implications - Higham, T; Barton, H; Turney, C; Barker, G; Ramsey, C; Brock, F (Wiley, 2009)
Subsamples of charcoal from a number of different excavation contexts at the early modern human (Homo sapiens) site of Niah Great Cave (Malaysia) were accelerator mass spectrometry (AMS) 14C dated. Samples were prepare using one of a number of different methods: untreated (control); acid-base-acid (ABA); and acid-base-wet oxidation with stepped combustion (ABOX-SC) after Bird et al. (1999). The results show that for material younger than ~ 25 ka BP there is little difference between the two chemical pretreatment methods and the control. For charcoal beyond ~ 25 ka BP, however, there are differences of up to 4000 a, with ABOX-SC ages being consistently older. This is argued to be a more effective pretreatment method for decontaminating charcoal samples prior to radiocarbon dating. For radiocarbon dating charcoals greater than ~ 25 ka BP, the ABOX-SC pretreatment and combustion approach appears to be the most rigorous method for developing a robust chronological framework for tropical sequences and should be more widely applied in contexts where the material being dated is likely to be ancient. The new chronology developed for Niah Cave may extend significantly earlier than this based on the recent discovery of lithics 50 cm below the earliest dated charcoal.